The activity and participation profile of persons with traumatic spinal cord injury in the Cape Metropole, Western Cape, South Africa : a prospective, descriptive study - Maclachlan, Mirda (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScPhysio)--Stellenbosch University, 2012.